2015
DOI: 10.1039/c5ra16405b
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a quercetin–gadolinium complex as an efficient positive contrast enhancer for magnetic resonance imaging

Abstract: The need for a highly effective contrast agent that aids in distinguishing normal and affected cells is in great demand in clinics for accurate diagnosis. In this context, the present study attempts to utilize the metal ion complexation capacity of a pharmacologically relevant dietary flavonol, quercetin for development of a novel MRI contrast agent. The flavonoidmetal complex was synthesized using quercetin dihydrate and gadolinium acetate and characterized by elemental analysis, spectroscopy techniques, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…Furthermore, some other studies have showed that Que has strong anticancer effect on a wide range of cancer cells such as acute lymphoid, myeloid leukemia cells, human gastric and colon cancer cells. [7][8][9][10][11] It is also reported that Que, IS and I3G have high antioxidant ability, 34 23,37 It must be noted that the concentrations (25, 50 and 100 μM) we used in this study may generally be not physiological and achievable in vivo because of the low bioavailability of these compounds. In this study we mainly investigated the anticancer-structure relationships between Que, IS and I3G in vitro and try to provide the foundation for high bioavailability and water solubility metabolites of quercetin in vivo evaluation, and to evaluate the potential clinical use of this study.…”
Section: Growth-inhibitory Effects and Cytotoxicity Of Que Is And I3mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some other studies have showed that Que has strong anticancer effect on a wide range of cancer cells such as acute lymphoid, myeloid leukemia cells, human gastric and colon cancer cells. [7][8][9][10][11] It is also reported that Que, IS and I3G have high antioxidant ability, 34 23,37 It must be noted that the concentrations (25, 50 and 100 μM) we used in this study may generally be not physiological and achievable in vivo because of the low bioavailability of these compounds. In this study we mainly investigated the anticancer-structure relationships between Que, IS and I3G in vitro and try to provide the foundation for high bioavailability and water solubility metabolites of quercetin in vivo evaluation, and to evaluate the potential clinical use of this study.…”
Section: Growth-inhibitory Effects and Cytotoxicity Of Que Is And I3mentioning
confidence: 99%
“…5,6 As one of the primary flavonoids, quercetin (3,3′,4′,5,7-pentahydroxyflavone) has been reported to have anti-tumor effect on many tumor cells, which may be related to catechol moiety in B ring and free hydroxyl groups in the quercetin structure. [7][8][9][10][11] Recent studies have showed that quercetin can be metabolized into various sulphated, glucuronidated and methylated forms in different organs, such as liver, kidney, colon and small intestine, and its metabolites may still act as antioxidants with higher hydrophily. 12 Our previous studies have also showed that QS (quercetin-5',8-disulfonate) can possess remarkably high anti-tumor activity in human breast cancer MCF-7 cells, 11 indicating that sulfated metabolites of quercetin may play an important role in cytotoxic effects.…”
Section: Introductionmentioning
confidence: 99%
“…The results acquired from the cell viability studies and oligonucleosomal fragmentation by DAPI staining indicated that the vanadium-rutin complex diminishes cell proliferation and encourages apoptosis both MCF-7 and MDA-MB-231 cells. One of the fundamental characteristics of anticancer agents is their capability to regulate cell cycle and which is achieved through the arrest of G1 and G2 phases (47). The style of apoptosis induced by vanadium-rutin complex was established by flow cytometric analysis using FITC tagged Annexin-V and PI staining.…”
Section: Discussionmentioning
confidence: 99%
“…MTT assay showed that complex ruthenium uvastatin can minimize cell proliferation and induce apoptosis. One of most important purposes of anticancer therapies is the modulation of the cell cycle, speci cally the inhibition of phases G1 and G2 plays a key role in the cell cycle cascade (84). To determine the complex's mechanistic approach to the induction of apoptosis, ow cytometric experiments were employed that made use of Annexin-V and PI staining procedures.…”
Section: Discussionmentioning
confidence: 99%